2016
DOI: 10.2147/copd.s96985
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vitamin D-binding protein polymorphisms and blood vitamin D level in Korean patients with COPD

Abstract: BackgroundIn chronic obstructive pulmonary disease (COPD), the blood vitamin D3 level is generally low, and genetic polymorphisms of vitamin D-binding protein encoded by the GC gene are associated with COPD development. In this study, we examined the relationship between GC polymorphisms and plasma vitamin D3 level in Korean patients with COPD.MethodsThe study included 175 COPD patients from the Korean Obstructive Lung Disease Cohort. Multivariate analysis was conducted with adjustment for age, body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The association between lung function and GRS was not affected by 25(OH)D levels, and the association between lung function and 25(OH)D levels were not affected by GRS. In line with our results, in a cohort of Korean COPD patients primarily consisting of males (97.7%), low 25(OH)D was associated with FEV1/FVC [ 43 ] regardless of rs4081 or rs7041 genotypes (both located on GC ). Coronary lesions [ 53 ] and tuberculosis [ 54 ] have also been associated with 25(OH)D levels, but not with vitamin D relevant SNPs.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The association between lung function and GRS was not affected by 25(OH)D levels, and the association between lung function and 25(OH)D levels were not affected by GRS. In line with our results, in a cohort of Korean COPD patients primarily consisting of males (97.7%), low 25(OH)D was associated with FEV1/FVC [ 43 ] regardless of rs4081 or rs7041 genotypes (both located on GC ). Coronary lesions [ 53 ] and tuberculosis [ 54 ] have also been associated with 25(OH)D levels, but not with vitamin D relevant SNPs.…”
Section: Discussionsupporting
confidence: 87%
“…One small study in Korean COPD patients, predominantly consisting of men, found that genotype was associated with vitamin D deficiency (25(OH)D < 20 ng/mL), but vitamin D deficiency was associated with lower FEV1/FVC, regardless of GC genotype. The genotypes of specific variants of SNPs rs4588 and rs7041 [ 43 ] were assessed in this study. These two SNPs are in strong linkage disequilibrium with rs2282679 assessed in our study and the results are similar to our results observed in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, serum levels of 25-OHD show seasonal variation. The prevalence of vitamin D deficiency is high during the winter months (28, 29). One limitation in the meta-analysis study showed that only one study contained African ethnicity (26), so this is considered the first study in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…VDBP is found in human cerebrospinal fluid [8] and is a serum protein encoded by the GC gene – the main carrier protein responsible for the transfer of calcitriol to target neurons [2]; however, little is known about the role of VDBP in the central nervous system [9]. Two common functional single nucleotide polymorphisms (SNPs) are present in exon 11 of the GC gene, and they result in nucleotide substitutions in codon 416 (GAT to GAG; Asp to Glu; rs7041) and codon 420 (AAG to ACG; Thr to Lys; rs4588) [10].…”
Section: Introductionmentioning
confidence: 99%